Destabilization of LiBH4 by MH2 (M = Ce, La) for hydrogen storage: Nanostructural effects on the hydrogen sorption kinetics - Gennari, Fabiana Cristina (2011)
Destabilization of LiBH4 by addition of metal hydrides or borohydrides is a powerful strategy to develop new promising hydrogen storage systems.  In this study, we compare the destabilization behavior of the LiBH4 by addition of MH2 (M= La, Ce). A notable improvement in the hydrogen desorption temperature, the rate and the weight percentage of hydrogen released is observed for LiBH4-MH2 respect to LiBH4. Formation of  LaB6 and CeB6 after dehydriding of the composites is proved by PXRD. Remarkable hydrogen storage reversibility of LiBH4-MH2 composites  is confirmed under moderate conditions: 400ºC and 6.0 MPa of hydrogen pressure for 4 h without catalyst. The LiBH4-LaH2 composite exhibits  improved hydrogen desorption performance compared with LiBH4-CeH2 composite, but the hydrogen storage reversibility is inferior. Notably, the  LiBH4-CeH2 nanocomposite produced by in situ formation of CeH2 from Ce(BH4)3-LiH displays excellent hydrogen storage properties. The  addition of ZrCl4 as a catalyst improves dehydriding kinetics. The mechanism underlying the enhancement in the LiBH4-MH2 composites is also discussed. Our study is the first work about reversible hydrogen storage in LiBH4-LaH2.